Praktik Tebus Murah Produk dengan Syarat Membeli Jenis Barang yang Ditentukan oleh Penjual - Mualim, Mualim; Hidayat, Yayat; Fauziyah, Aulia Tsamrotul (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
The practice of cheap redemption of products is one form of promotion in a company including in Indomaret Cipicung District, Kuningan Regency, where in its implementation consumers must meet the total shopping requirements determined by Indomaret Cipicung District, Kuningan Regency. However, it is not yet known exactly how the practice of cheap redemption of products at Indomaret Cipicung District, Kuningan Regency and how Islamic law reviews the practice of cheap redemption of these products. This study aims to determine how the practice of cheap redemption of products at Indomaret Cipicung District, Kuningan Regency and this study aims to analyze the review of Islamic law on the practice of cheap redemption carried out at Indomaret Cipicung District, Kuningan Regency. This research is qualitative research and also includes the type offield research. Data collection techniques using interviews with staff and consumers of Indomaret Cipicung District, Kuningan Regency and documentation. The results of this study are first, the practice of cheap redemption of products at Indomaret Cipicung District is a form of reward or appreciation to consumers for reaching total shopping at Indomaret. Second, based on the review of Islamic law, the practice of cheap redemption of products at Indomaret Cipicung District, Kuningan Regency has fulfilled the pillars and legal requirements of buying and selling. In addition, the practice of cheap redemption of these products also has no element of coercion.